Scope of Spirituality Research in Occupational Therapy Literature: A Scoping Review Study - Masoud Babaei; Mehdi Rassafiani (Vesnu Publications, 2017)
Introduction: Spirituality leads people to seek for life meaning and life purpose. Occupational therapy (OT) is a holistic profession that believes all of experienced aspects of human including physical, psychological, social and spiritual aspects are important to the health of human being. However, the general consensus is that occupational therapy literature has not paid enough attention to the concept of spirituality. Therefore, purpose of this article was to present the extent and nature of research about spirituality in that occupational therapy and finding gaps in this area. Materials and Methods: A scoping review method was used. Biomedical and rehabilitation databases were searched using the relevant keywords. The interval of search was from the first articles of database till October 2015. Results: Forty five papers were entered in this review. They included original articles (46.6%), review and teaching articles (29.0%), books and book chapters (8.8%), models and theories (8.8%), and viewpoints (8.8%). Conclusion: This review showed the extent of research about spirituality in that occupational therapy. Spirituality is an important aspect of occupational therapy literature, but there are few papers and researches in this subject. Overall, this review showed that there was a paucity of studies about spirituality in occupational therapy. These studies were often about the role of spirituality and perspective of occupational therapists toward it, and there was little attention to the concept of spirituality, its definition, available interventions, and procedure of facing with spiritual needs of clients.